Influence of access to an integrated trauma system on in-hospital mortality and length of stay. Issue 7 (July 2015) - Kuimi, Brice L. Batomen; Moore, Lynne; Cissé, Brahim; Gagné, Mathieu; Lavoie, André; Bourgeois, Gilles; Lapointe, Jean
Abstract Background Few data are available on population-based access to specialised trauma care and its influence on patient outcomes in an integrated trauma system. We aimed to evaluate the influence of access to an integrate trauma system on in-hospital mortality and length of stay (LOS). Methods All adults admitted to acute care hospitals for major trauma [International Classification of Diseases Injury Severity Score (ICISS < 0.85)] in a Canadian province with an integrated trauma system between 2006 and 2011 were included using an administrative hospital discharge database. The influence of access to an integrated trauma system on in-hospital mortality and LOS was assessed globally and for critically injured patients (ICISS < 0.75), according to the type of injury [traumatic brain injury (TBI), abdominal/thoracic, spine, orthopaedic] using logistic and linear multivariable regression models. Results We identified 22, 749 injury admissions. In-hospital mortality was 7% and median LOS was 9 days for all injuries. Overall, 92% of patients were treated within the trauma system. Globally, patients who did not have access had similar mortality and LOS compared to patients who had access. However, we observed a 62% reduction in mortality for critical abdominal/thoracic injuries (odds ratio = 0.38; 95% CI, 0.16–0.92) and an 8% increase in LOS for TBI patients (geometric mean ratio = 1.08; 95% CI, 1.02–1.14) treated within the trauma system. Conclusions Results provides evidence that in a health system with an integrated mature trauma system, access to specialised trauma care is high and the small proportion of patients treated outside the system, have similar mortality and LOS compared to patients treated within the system. This study suggests that the Québec trauma system performs well in its mandate to offer appropriate treatment to victims of injury that require specialised care.